التغير القيمي وأثره على اتجاهات الشباب في المجتمع الجزائري بين الواقع والتحديات المستقبلية - بن رمضان, سامية (Sciences de l'Homme et de la Société, 2013)
يهدف هذا البحث على ابراز تاثير التغيرات القيمية على مستوى اتجاهات الشباب الجزائري، بغرض فهم الأبعاد الايجابية والسلبية لهذه التأثيرات على مستوى اتجاهات الشباب داخل النسق الاجتماعي الذي ينتمي إليه، ومواجهة التحديات المستقبلية..وقد خلص البحث إلى جملة من النتائج تتمحور حول وجود تأثيرات متبانة بين ما هو ايجابي وسلبي على اتجاهات الشباب الجزائري. وتكمن هذه التأثيرات في الجانب السلبي والمتمثل في التناقض بين القيم التقليدية والقيم الجديدة أي يعيش الشباب تناقضا بين ما يتعلمه من مجتمعه وبين ما يزينه له الغرب، في حين تملت التاثيرات من الجانب الايجابي في الارتباط بالقيم المميزة للمجتمع الجزاري.   This research aims to highlight the impact of value changes on the level of Algerian youth trends, in order to understand the positive and negative dimensions of these effects on the level of youth trends within the social pattern to which it belongs and on how to face the challenges of the future.    The research found a number  of  results centered around the presence of different impacts between what is positive and negative for  Algerian youth orientations. These impacts reside  in the negative side which is characterized by  the contradiction between traditional values and the new values, which means that the young lives contradiction between what he learns from society and what the West adorns for him, while  the positive side is represented by the abiding by the distinctive values of the Algerian society.